Strategi Komunikasi PT Telkom Witel Denpasar Bali dalam Menghadapi Keberadaan Media Online: Communication Strategy of PT Telkom Witel Denpasar Bali in Facing the Existence of Online Media - Febryanto Rakhmat Hanafi; Sutrisno; Abdul Rahman (Al-Gafari : Manajemen dan Pendidikan, 2026)
This study examines and discusses the Communication Strategy carried out by PT Telkom Witel Denpasar Bali. PT Telkom Witel Denpasar Bali in providing services to the community has various communication strategies used in promotional activities such as holding events on certain celebration days, door to door, distributing brochures and seminars to attract consumers. The purpose of this study is to determine the communication strategy of PT Telkom Witel Denpasar Bali in serving the community. The method used is a qualitative approach method where researchers require data used by researchers, namely descriptive qualitative approach is used because the data needed by the author is only in the form of information and explanations from informants. The data needed in this study were obtained through information from the General Manager of PT Telkom, customer service and officers. In collecting data, researchers used several techniques, namely observation, interviews, and documentation. The collected data were analyzed by data reduction, data presentation (Displey), and data verification or drawing conclusions. From the research results, it can be concluded that the communication strategy of PT Telkom Witel Denpasar Bali has five strategic parts used, namely Research, Planning, Execution, Measurement or Evaluation, Report. The obstacles to the Communication Strategy of PT Telkom Witel Denpasar Bali in facing the existence of Online Media are the factors of message sender, Media and Channels.